39
$\begingroup$

Evaluate the integral: $$ \int_0^1 \left(\sqrt[3]{1-x^7} - \sqrt[7]{1-x^3}\right)\;dx$$

The answer is $0,$ but I am unable to get it. There is some symmetry I can not see.

$\endgroup$
  • 3
    $\begingroup$ Generally speaking, $$\int_0^1 \sqrt[m]{1-x^n}dx = \int_0^1 \sqrt[n]{1-x^m}dx = \frac{\frac{1}{m} ! \cdot \frac{1}{n} !}{\left(\frac{1}{m} + \frac{1}{n}\right) !}$$ where $$\frac{1}{n} ! = \int_0^\infty e^{-x^n}dx$$ See here and here for more details. $\endgroup$ – Lucian Oct 14 '13 at 23:16
61
$\begingroup$

Let $m, n > 0$. Then observe that $$ \int_{0}^{1} \sqrt[n]{1-x^m} \; dx$$ is the area of the region given by inequalities $$ 0 \leq x \leq 1 \quad \text{and} \quad 0 \leq y \leq \sqrt[n]{1-x^m}.$$ But the last inequality is equivalent to $0 \leq x^m + y^n \leq 1$. Thus $$ \int_{0}^{1} \sqrt[n]{1-x^m} \; dx = [\text{Area given by} \ 0 \leq x^m + y^n \leq 1, \ 0 \leq x, y \leq 1 ]$$ Thus by interchanging the role of $x$ and $y$, we have $$ \int_{0}^{1} \sqrt[n]{1-x^m} \; dx = \int_{0}^{1} \sqrt[m]{1-x^n} \; dx.$$


Of course, we can give a purely analytic approach. Let $y = \sqrt[3]{1 - x^7}$. Then $x = \sqrt[7]{1 - y^3}$ and hence by integration by substitution, $$\begin{align*} \int_{0}^{1} \sqrt[3]{1 - x^7} \; dx &= \int_{0}^{1} y(x) \; dx \\ &= \int_{1}^{0} y \; dx(y) \\ &= [y x(y)]_{1}^{0} - \int_{1}^{0} x(y) \; dy \\ &= \int_{0}^{1} \sqrt[7]{1 - y^3} \; dy. \end{align*}$$

$\endgroup$
  • 10
    $\begingroup$ Formally (and not only formally), we know that $d(xy)=x\, dy + y \, dx$ Hence $xy = \int x \, dy + y \, dx$. This is an abstract way to compute the integral of a function provided we know the integral of its inverse. $\endgroup$ – Siminore May 1 '12 at 15:37
  • 2
    $\begingroup$ @Siminore: The way you demonstrated is very clear and systematic. All the scattered understandings on this kind of integral are now integrated. Thanks. $\endgroup$ – Sangchul Lee May 1 '12 at 15:58
3
$\begingroup$

Another way to go is to use $\beta$-function

$$ \mathrm{\beta}(x,y) = \int_0^1t^{x-1}(1-t)^{y-1}\,dt,\quad {Re}(x),{Re(y)}>0. $$

$$ \int_0^1 \sqrt[3]{1-x^7} \mathrm dx = \frac{1}{7}\int_0^1 u^{-6/7}(1-u)^{1/3} \mathrm dx=\dots\,. $$

Now, you can finish the problem.

$\endgroup$
1
$\begingroup$

Observing the inverse of the function $f(x) = \sqrt[3]{1 - x^7}$ on the interval $[0,1]$ is $f^{-1} (x) = \sqrt[7]{1 - x^3}$, using the result $$\int^b_a f(x) \, dx + \int^{f(b)}_{f(a)} f^{-1} (x) \, dx = b f(b) - a f(a),$$ since $f(a) = f(0) = 1$ and $f(b) = f(1) = 0$ it immediately follows that $$\int^1_0 \sqrt[3]{1 - x^7} \, dx + \int^0_1 \sqrt[7]{1 - x^3} \, dx = 0,$$ or $$\int^1_0 \left \{\sqrt[3]{1 - x^7} - \sqrt[7]{1 - x^3} \right \}\, dx = 0.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.